2010
DOI: 10.1007/s00330-010-1888-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac chamber quantification using magnetic resonance imaging at 7 Tesla—a pilot study

Abstract: This pilot study demonstrates that cardiac chamber quantification at 7 T using FGRE is feasible and agrees closely with SSFP at 1.5 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
51
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 28 publications
8
51
2
Order By: Relevance
“…11 However, only a limited amount of research on ultra-highfield (7 T) body imaging has been reported within the last few years, mostly focusing on 7 T cardiac MRI. [12][13][14][15][16][17][18] These promising preliminary results demonstrate the high potential of ultra-high-field imaging. To our knowledge, no other study demonstrating the feasibility of Gd-enhanced 7 T abdominal imaging has yet been published.…”
mentioning
confidence: 83%
“…11 However, only a limited amount of research on ultra-highfield (7 T) body imaging has been reported within the last few years, mostly focusing on 7 T cardiac MRI. [12][13][14][15][16][17][18] These promising preliminary results demonstrate the high potential of ultra-high-field imaging. To our knowledge, no other study demonstrating the feasibility of Gd-enhanced 7 T abdominal imaging has yet been published.…”
mentioning
confidence: 83%
“…This caveat can be relaxed by using many element coil arrays tailored for cardiac MR [60]–[64] or by moving to CMR at magnetic field strengths of B 0 ≥3.0 T [64]–[69].…”
Section: Discussionmentioning
confidence: 99%
“…While most of the scanners currently used in clinics are of 1.5-3 T, higher magnetic fields can now be reached. 15-20 T scanners have become available, mostly for animal studies but also for human, especially in neurological [3], musculoskeletal [4], or cardiac [5] imaging where high sensitivity and resolution are required. These hardware improvements come along with software evolutions and with the design of new RF pulse sequences, allowing visualization of tissues of interest with increasing accuracy and sensitivity by, for example, suppression of unwanted tissue signal during image acquisition or by making possible the production of three-dimensional images.…”
Section: Gadolinium As a Contrast Agent In Mrimentioning
confidence: 99%